Infestation of Xystrocera festiva in Paraserianthes falcataria plantation in East Java, Indonesia - Endang A. H. (2015)
Sengon (Paraserianthes falcataria) is an exceptionally fast-growing tree species native to eastern Indonesia and Papua New Guinea. A serious problem encountered by sengon plantation in western Indonesia is the infestation of stem borer (Xystrocera festiva, Coleoptera, Cerambycidae). This study was aimed at characterising the borer infestation. The per cent of insect infestation increased with age of the stand. The rate of damage was affected by the number of larvae and/or boring tunnels. Xystrocera festiva can infest all diameters of trees at a certain age of sengon stand. The damaged parts of the tree were located between 3.4 and 7.5 m above the ground.